Theoretical and computational chemistry aspects - Ramasami, Ponnadurai (Chemical sciences in the focus, 2021)
Based on "The Virtual Conference on Chemistry and its Applications (VCCA-2020) - Research and Innovations in Chemical Sciences: Paving the Way Forward" held in August 2020 and organized by the Computational Chemistry Group of the University of Mauritius. The chapters reflect a wide range of fundamental and applied research in the chemical sciences and interdisciplinary subjects.